2021
DOI: 10.1038/s41467-021-25593-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic exploration of sulfinyl radicals using sulfinyl sulfones

Abstract: Sulfinyl radicals – one of the fundamental classes of S-centered radicals – have eluded synthetic application in organic chemistry for over 60 years, despite their potential to assemble valuable sulfoxide compounds. Here we report the successful generation and use of sulfinyl radicals in a dual radical addition/radical coupling with unsaturated hydrocarbons, where readily-accessed sulfinyl sulfones serve as the sulfinyl radical precursor. The strategy provides an entry to a variety of previously inaccessible l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 54 publications
1
41
0
1
Order By: Relevance
“…Xu et al reported a thiosulfonates of aryl alkynes to deliver (E)‐(β)‐arylthiolvinyl sulfones exclusively [7] . Despite these advances, thiosulfonylation of alkynes involving the formation of C−SO 2 and another C−SO bond simultaneously has only one example [8d] . Building on our continuous interest in the difunctionalization of alkynes, [8,4c,5a] we here reported the sulfinylsulfonation of alkynes using sodium sulfinate and TMSCl, affording a simple and efficient method to access the β‐sulfinyl alkenylsulfone products (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al reported a thiosulfonates of aryl alkynes to deliver (E)‐(β)‐arylthiolvinyl sulfones exclusively [7] . Despite these advances, thiosulfonylation of alkynes involving the formation of C−SO 2 and another C−SO bond simultaneously has only one example [8d] . Building on our continuous interest in the difunctionalization of alkynes, [8,4c,5a] we here reported the sulfinylsulfonation of alkynes using sodium sulfinate and TMSCl, affording a simple and efficient method to access the β‐sulfinyl alkenylsulfone products (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…During preparation of this manuscript, our group also reported a related sulfinylsulfonation of alkyne, utilizing sodium sulfinate/CH 3 COCl for radical generation. However, this condition didn't tolerate nucleophilic groups such as OH, NH 2 and COOH [8d] …”
Section: Introductionmentioning
confidence: 99%
“…5 Given the highly synthetic and pharmaceutical importance of these compounds, the development of mild and efficient approaches to access these sulfones remains a topic of great interest among organic chemists. 6 2,3-Disulfonylpropenes, which contain both the vinyl sulfone and the allyl sulfone structural units, have emerged as versatile synthons in organic synthesis and medicinal chemistry. Although methodologies for the construction of vinyl sulfones and allyl sulfones have been well developed, respectively, to date, protocols for directly accessing disulfonyl compounds, 7 as well as propargyl sulfones, 8 from alkynes are quite rare (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…9 Aside from the involvement in atmospheric chemistry, sulfinyl radicals are useful intermediates in synthetic sulfur chemistry for their broad applications in assembling valuable sulfoxide compounds. 10 Among sulfur-centered radicals, the prototypical alkylsulfinyl radical CH 3 SO was detected in the O 2 -oxidation of DMS. 6a Its molecular structure and reactivity have been the focus of comprehensive experimental and computational studies.…”
Section: Introductionmentioning
confidence: 99%